Prevalence of Small Intestine Cestodes in Goat at Pegirian Slaughterhouse Surabaya - Bryan Ahmad Affan Lubis; Setiawan Koesdarto; Eka Pramyrtha Hestinah; Kusnoto Kusnoto; Lucia Tri Suwanti (Journal of Parasite Science (JoPS), 2019)
This study was conducted to determine the prevalence of small Intestine cestodes in goat at Pegirian Slaughterhouse Surabaya with gastrointestinal dissection method. Thirty-six samples of goat’s small intestine, twenty-five from Kacang goats and eleven from Ettawa-cross (PE) goats, were collected from Pegirian Slaughterhouse Surabaya on May 2018. Fresh adult worms were collected with gastrointestinal dissection and microscopically identified. The result showed that cestodes infections could be identified in three (12%) of Kacang goats and three (27.27%) of PE goats. The cestode infections were identified five positive samples (19.23%) in male goat and one positive sample (10%) in female goat, while determined by the ages found three positive samples (17.64%) in under two years old goats and three positive samples (15.78%) in more than or equal two years old goats. The Chi-Square statistical test (p >0.05) showed there was no significant correlation from the race, sex, and ages of goats on the prevalence of Moniezia expansa.